Capacity sharing approaches in multi-tenant, multi-service PONs for low-latency fronthaul applications based on cooperative-DBA - Ruffini, Marco (My University, 2020)
We propose and compare algorithms to allocate upstream PON capacity, where multiple virtual operators generate independent frame-level allocation over shared infrastructure. Our fragmentation-based approach shows the ability to limit latency increase to a few microseconds.
Optical Fibre Communications (OFC)
PUBLISHED
Keywords: Passive optical networks; 5G networks; Networks optimisation; Fiber optics communications